2020
DOI: 10.1111/cod.13663
|View full text |Cite
|
Sign up to set email alerts
|

Intense skin reaction to a new glucose monitoring and insulin pump system

Abstract: Avoidance of nickel and colophonium was initiated: the metalbracket chin-pad was replaced by a chin-pad with plastic brackets and she began to use a hypoallergic artificial rosin oil without colophonium. After treating the existing lesions with topical corticosteroids and the start of the avoidance measures, no recurrence was observed during 6 months follow-up. DISCUSSION ACD results in a considerable burden in professional musicians. Several case reports described ICD ("fiddler's neck" type 1) while others re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 9 publications
0
47
0
Order By: Relevance
“…Such a pattern of reactivity might have indicated a possibility of a colophony‐related culprit contact allergen in Dexcom G6. Different colphony derivatives may be used as tackifiers in pressure‐sensitive acrylate‐based adhesives 26,31 . The GC‐MS analyses indicated the presence of methyldehydroabietate in the extract of the adhesive patches, which in turn indicate the presence of colophony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a pattern of reactivity might have indicated a possibility of a colophony‐related culprit contact allergen in Dexcom G6. Different colphony derivatives may be used as tackifiers in pressure‐sensitive acrylate‐based adhesives 26,31 . The GC‐MS analyses indicated the presence of methyldehydroabietate in the extract of the adhesive patches, which in turn indicate the presence of colophony.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts were analysed by gas chromatography‐mass spectrometry 26 . Dilutions of IBOA in acetone were used as reference standards.…”
Section: Methodsmentioning
confidence: 99%
“…Case 2 was further exposed to IBOA through the use of Omnipod 21 and was most likely thereby sensitized to colophony and hydroabietyl alcohol, causing allergic contact dermatitis almost instantly when using the Medtrum devices. 4 The three cases are particularly interesting since they could at first use the device without experiencing any skin problems, in cases 2 and 3, even for a prolonged time, and then experienced dermatitis. The fact that we know from previous investigations and the investigations reported here that in Dexcom G6 2 both IBOA and possibly colophony-related substances are present, but presumably in our cases the concentration did not initially initiate an elicitation.…”
Section: Discussionmentioning
confidence: 99%
“…She was investigated because of contact dermatitis and found to have an allergic contact dermatitis. 4 Because of the multiple contact allergies found in the earlier investigation (Table 1), and the fact that the patient now had started having symptoms from Dexcom G6, she was once more referred for patch testing.…”
Section: Methodsmentioning
confidence: 97%
“…Analysis of the two extracts using gas chromatography–mass spectrometry 5 showed that both samples contained DBM and DBF. The presence was confirmed by analysis of the pure substances.…”
Section: Case Reportmentioning
confidence: 99%